2018
DOI: 10.1029/2018gl080619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mainshock on the Size Distribution of the Aftershocks

Abstract: A systematic decay of the aftershock rate over time is one of the most fundamental empirical laws in Earth science. However, the equally fundamental effect of a mainshock on the size distribution of subsequent earthquakes has still not been quantified today and is therefore not used in earthquake hazard assessment. We apply a stacking approach to well‐recorded earthquake sequences to extract this effect. Immediately after a mainshock, the mean size distribution of events, or b value, increases by 20–30%, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 52 publications
10
64
2
Order By: Relevance
“…This study therefore does not address any potential issues of selection bias within the original data set. I also do not revisit postmainshock b ‐value increases (Gulia et al., 2018), as b ‐value increases are in the opposite direction of the expected bias, and there is no reason to doubt those b ‐value measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study therefore does not address any potential issues of selection bias within the original data set. I also do not revisit postmainshock b ‐value increases (Gulia et al., 2018), as b ‐value increases are in the opposite direction of the expected bias, and there is no reason to doubt those b ‐value measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued that b ‐value may carry diagnostic information about the state of stress on the faults generating the earthquakes (Amitrano, 2003; Gulia et al., 2018; Scholz, 2015; Schorlemmer et al., 2005; Spada et al., 2013). This has led to the idea that b has potential for discriminating between foreshock and aftershock sequences (Gulia & Wiemer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For small data sets parsimonious multivariate models should ideally be developed as well, to address the joint distribution of interevent times, distances and magnitudes 60 , which is ignored in our current approach. This should complement spatio-temporal ETAS models that can effectively be used when enough data are available.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, Gulia and Wiemer, together with co-workers, found that the b value normally rises during an aftershock sequence, which means that small earthquakes become more common 5 . In the present work, the authors noticed that, occasionally, the b value drops instead of rising, implying that big quakes increase in frequency.…”
Section: E M I Ly E B R O D S K Ymentioning
confidence: 93%